Optimization of Information Security Standard Operating Procedures for The Academic Information System at Sebelas April University - Hidayat, Eka; Prasetyo Utomo, Hadi; Suwarningsih, Wiwin (LPPM & Fakultas Teknologi Informasi UNSAP, 2025)
The Academic Information System at Sebelas April University housed various essential data, including student information, faculty information, and academic records. These data were susceptible to cybersecurity threats, data breaches, and unauthorized access, potentially disrupting academic processes and tarnishing the university's reputation. This study aimed to enhance the security of UNSAP's Academic Information System by optimizing the Standard Operating Procedures for information security. A descriptive qualitative research method was employed to analyze the current information security conditions and formulate recommendations for improving the Standard Operating Procedures. The Octave Allegro approach and the ISO 27001:2022 standard served as frameworks in this study. The analysis revealed that the existing Standard Operating Procedures for information security were inadequate. Consequently, new, more comprehensive Standard Operating Procedures were developed, encompassing access control, data management, incident handling, and data backup. These new Standard Operating Procedures were expected to bolster the security of UNSAP's Academic Information System and assist UNSAP in complying with applicable information security standards.